Green Technology Model Based On Environmental Protection (International Journal of Innovative Research in Engineering & Management, 2021)
Serious societal issues are the primary cause of pollution,  environmental deterioration and depletion of resources.  Integration of green technological innovation is necessary  only in tightly linked technological innovation and  environmental security to ensure sustainable social economic  development. Green technology advancement is an  environmental economic endeavor that has a major effect on  the accomplishment of self-sustaining scientific, financial,  social and natural development. Green technological  advancement with external impact features, complexity,  specialization and commercial failure implies the appropriate  system structure of green technology innovation. A secondary  function, which removes uncertainties, internalizes economic  externality and reduces transaction costs, is employed  primarily to promote the limiting and guiding feature of  development in the device. This paper presents a fundamental  framework for the improvement of the environment systems,  from the perspective of the green technology innovation  model, including improvements in environmental legislation  and law, comparison studies of innovation in green  technology and traditional technological innovation.
Keywords: Decentralization; Economic; Environmental System; Green Technology; Technology Innovation